Association of West African ancestry and blood pressure control among African Americans taking antihypertensive medication in the Jackson Heart Study. Issue 2 (12th February 2020) - Van Tassell, Jon C.; Shimbo, Daichi; Hess, Rachel; Kittles, Rick; Wilson, James G.; Jorde, Lynn B.; Li, Man; Lange, Leslie A.; Lange, Ethan M.; Muntner, Paul; Bress, Adam P.
Abstract: African Americans have a wide range of continental genetic ancestry. It is unclear whether racial differences in blood pressure (BP) control are related to ancestral background. The authors analyzed data from the Jackson Heart Study, a cohort exclusively comprised of self‐identified African Americans, to assess the association between estimated West African ancestry (WAA) and BP control (systolic and diastolic BP < 140/90 mm Hg). Three nested modified Poisson regression models were used to calculate prevalence ratios for BP control associated with the three upper quartiles, separately, vs the lowest quartile of West African ancestry. The authors analyzed data from 1658 participants with hypertension who reported taking all of their antihypertensive medications in the previous 24 hours. WAA was estimated using 389 ancestry informative markers and categorized into quartiles (Q1: <73.7%, Q2: >73.7%‐81.0%, Q3: >81.0%‐86.3%, and Q4: >86.3%). The proportion of participants with controlled BP in the lowest‐to‐highest WAA quartile was 75.2%, 76.1%, 76.6%, and 74.4%. The prevalence ratios (95% CI) for controlled BP comparing Q2, Q3, and Q4 to Q1 of WAA were 1.00 (0.93‐1.08), 1.02 (0.94‐1.10), and 0.99 (0.91‐1.07), respectively. Among African Americans in the Jackson Heart Study taking antihypertensive medication, BP control rates did not differ across quartiles of WAA.